Rachunek przepływów pieniężnych jako odrębny przedmiot na studiach ekonomicznych - Krzeszowski, Wojciech Dawid (Cash-Flow Statement as a Subject at Schools of Economics, 2005)
Graduates of schools of economics usually have an extensive knowledge of the balance sheet and the income statement. At the same time they have a general knowledge of the cash-flow statement. As the author's experience shows, in practice accountants find it most difficult to prepare the discussed element of the financial statement. Similarly, business managers tend to limit their financial analysis to 'looking through' the balance sheet and the income statement. This most frequently stems from their inability to interpret the cash-flow statement. Financial department staff also find it difficult to prepare cash-flow plans and link them with the remaining pieces of the financial planning. Taking the aforementioned into account, it seems essential that more attention be paid to the issue of the cash-flow statement both ex post and ex ante. The issue - in its assumptions - would broaden the students' knowledge of the cash-flow statement and at the same time provide a link between accounting (which interprets transactions on the accrual basis) and finances (which puts major emphasis on the cash-flow aspect).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 92-97